Literature Review: Factors Influencing Creativity in Junior High School Students’ Science Learning - Chova, Septiza Kurnia; Muttaqiin, Arief; Oktavia, Rani (Pendidikan IPA, FMIPA, UNP, 2025)
Creativity refers to the ability to generate novel ideas and skills from ordinary situations, characterized by fluency, flexibility, and originality. Creative students continuously seek innovative ways to address problems in their daily lives. In the context of science education, such students tend to find creative science problems easier to solve, as they already possess effective problem-solving strategies. This study employs a literature review method by analyzing 16 selected articles from Google Scholar that met specific inclusion criteria. The main objectives of this research are to (1) evaluate the creativity levels of Indonesian high school students in science learning and (2) identify the factors that influence their creativity in this field. The findings reveal that the overall creativity level of Indonesian high school students is categorized as low, contrasting with the expected higher level. Factors affecting students’ creativity include the implementation of diverse learning models, teachers’ pedagogical competence, and students’ comprehension of the subject matter.